Manufacture of complex heart tissues: technological advancements and future directions - Yihan Zhang (AIMS Bioengineering, 2021)
The latest technological advances in stem cell biology and mechanical engineering provide new opportunities for cardiac tissue engineering, enabling the production of highly efficient differentiated cells and the manufacture of high-resolution complex cardiac tissues. In this review, we summarize the progress of stem cell technology in 3D bioprinting of heart tissue and the latest technological breakthroughs. The main topics discussed include somatic cell reprogramming, differentiation of induced pluripotent stem cells (iPSCs), 3D bioprinting strategies, bioinks, and in vitro vascularization methods. The objective of this review is to explore the possibility of interdisciplinary research to solve the existing challenges in tissue engineering by summarizing the existing work and progress and pointing their current limitations.